ICT platforms for Indonesian EFL students viewed from gender during the COVID-19 pandemic - Eka Apriani; Safnil Arsyad; Syafryadin Syafryadin; Dadan Supardan; Paidi Gusmuliana; Santiana Santiana (Studies in English Language and Education, 2022)
The aims of this study are to find out (1) ICT (Information and Communications Technology) platform used by male and female students from Islamic universities in Indonesia, (2) their perception of using ICT, and (3) their barriers to using ICT in English language learning during the COVID-19 pandemic. The data was collected from an online questionnaire (Google Form) from students majoring in English from seven Islamic universities in Indonesia. There were 30 male students and 30 female students from every university who participated in this research, making a total of 210 student respondents. The data were analyzed quantitatively by using the SPSS computer program. First of all, female students used more various types of ICT platforms compared to male students. Second, the female students viewed ICT use more positively than male students in language learning. And lastly, even though the females deemed ICT more optimistically compared to male students, nevertheless the females encountered more barriers in using the ICT platforms compared to the male students in this study. Again, even though male students were more skillful in ICT literacy than female students, female students constructively regarded ICT use in language learning as more beneficial to them in terms of skill, knowledge, and motivational improvement.